Effect of different load of shoulder external rotation exercises on changes in muscle activity and exerted torque - Saeki, Yurika; Kubota, Atsushi; Kishimoto, Kohei; Inoue, Mika; Inoue, Takumi; Takazawa, Yuji (Frontiers in Sports and Active Living, 2025)
The effects of shoulder external rotation exercises on the EMG amplitude of the infraspinatus, and teres minor, and torque in healthy individuals remain uncertain. In this study, we aimed to determine the effects of varying loads during shoulder external rotation exercises on exerted torque and muscle activity of the infraspinatus, teres minor, and deltoid. Twenty-four upper limbs from 12 healthy adult males (22.5 ± 1.9 years) were included. Participants performed shoulder external rotation exercises with low-, medium-, and high-load conditions using elastic bands of three different tensions. The number of exercises was set so that the total workload during the exercise was equal for each loading condition. The torque of the shoulder external rotation and electromyography (EMG) amplitude of the infraspinatus, teres minor, and the posterior deltoid were measured during the concentric shoulder external rotation task, before and after the exercise. In addition, the muscle activity ratio of the three muscles was calculated. Analysis divided into 30° intervals, under the low-load condition, shoulder external rotation torque and EMG amplitude of the infraspinatus and teres minor did not change; However, the EMG amplitude of the posterior deltoid increased significantly. The muscle activity ratio in the posterior deltoid showed exercise range × time interaction, with a significant increase from pre-exercise (Pre) (13.59 ± 5.70%) to 20 min after the exercise (15.40 ± 6.03%) in the 61°–90° external rotation range. In the medium- and high-load conditions, the EMG amplitude significantly increased for all muscles. However, under the medium-load condition, significant differences were observed between 0–30° (Pre: 25.4 Nm, 20 min: 26.0 Nm), 31–60° (Pre: 24.3 Nm, 20 min: 25.4 Nm), and 61–90° (Pre: 23.7 Nm, 20 min: 24.6 Nm). There was also an increase in the muscle activity ratio in the posterior deltoid, with a main effect on time in the medium load condition (p < 0.05). The changes in torque, EMG amplitude, and muscle activity ratio after the shoulder external rotation exercises were not uniform across different exercise loads. Therefore, it is necessary to use different tensions depending on the purpose of the exercise.